The prevalence of substance use among contact sport participants in High Schools in Iceland - Silja Rut Rúnarsdóttir 2002- (2024)
Alcohol and drug use represent a potentially important deterrent to sport participation and engagement. The aim of this study was to examine the prevalence of substance use among contact sport participants in high schools in Iceland compared to those students who do not participate in contact sports. Randomly selected data from the population-based Youth in Iceland 2018 survey were used for the study analysis. The sample was = 1966, 50.4% males and 49.6% females, born between 1998 – 2003. The main results showed that when the frequency of training in contact sports is four times or more per week, there is a negative association with all the substances examined for both genders. Among the girls who participated once to three times per week, all substance use decreased compared to non-participants, but among the boys, the results were more mixed; in some cases, substance use increased compared to non-participants. Previous studies on the relationship between participation in sports and substance use vary considerably. In the critical literature review of this study, many researchers indicated a positive relationship between participation in sports and substance use. Therefore, studying this relationship further with Iceland's adolescents and young adults would be interesting. Keywords: Contact sports, substance use, frequency, gender, adolescents Notkun áfengis og vímuefna getur verið afdrifarík hindrun við íþróttaiðkun. Markmið þessarar rannsóknar er að kanna algengi vímuefnanotkunar meðal þátttakenda í snertiíþróttum í framhaldsskólum á Íslandi samanborið við þá nemendur sem ekki hafa stundað snertiíþróttir. Stuðst var við gögn sem valin voru af handahófi úr spuningakönnuninni Ungt fólk 2018. Úrtakið við greiningu gagnanna var 1966 þátttakendur, 50,4% karlar og 49,6% konur sem voru fædd á árunum 1998 – 2003. Helstu niðurstöður voru þær að þegar tíðni æfinga í snertiíþróttum er fjórum sinnum eða oftar í viku fundust neikvæð tengsl við öll vímuefnin sem skoðuð voru hjá báðum kynjum. Meðal stúlkna sem sögðust æfa ...